Experimental And Numerical Investigation For Cooling Performance Of High Power Light Emitting Diode (Led) Arrays Using Heat Sink - Mohamad, Muhammad Sofwan (2012)

(untitled)
High power light emitting diodes (LEDs) are increasingly used in many lighting applications due to their significant advantages over conventional light sources, which include long lifetime, low energy consumption and high efficiency. In order to match light output of conventional light sources, multiple LEDs are essential in application to lighting systems. However, this solution would escalate junction temperature, which significantly degrades the performance and shortens the lifetime of LED. Therefore, thermal management plays very important role in designing LED lighting system. The main aim of the present study is to investigate the cooling performance of high power LED arrays, attached to a typical heat sink as cooling means. This was accomplished by performing an experimental and numerical investigation using four different types of LED array arrangements. The LED placement incorporated the basic shapes of square, circular, triangular and hexagonal grid. An experiment set up was developed to test the heat transfer performance of the LED arrays with laminar air flow at various Reynolds number (Re) ranging from 0 to 21173. The parameters such as thermal resistance, heat transfer coefficient and Nusselt number (Nu) were examined in the experiments. Study carried on the effect of Re showed that the overall heat transfer performance of the lighting systemsincreased significantly for Re up to 15880 and less effects were noticed by increasing Re to 21173. Subsequent tests were carried out on the effect of different type of LED arrays. The results showed that array C was found to give the best cooling performance when operated under natural and forced convection conditions due to xix the good heat transfer capability. Moreover, three dimensional (3D) simulations using Computational Fluid Dynamics (CFD) code has been used to predict the flow characteristic, pressure drop and temperature distribution. The code applied finitedifferent method (FDM) based on Navier-Stokes equations (NSEs) and heat transfer equations to solve the steady, laminar flow whereas the pressure term was solved using Marker and Cell (MAC) method. MicroAVS® software was utilized to visualize the numerical results. The temperature and heat transfer coefficient from numerical investigation was then compared with the experimental findings and a reasonable agreement was obtained.